Edukasi Kesehatan Dalam Pemanfaatan Tanaman Kunyit (Curcuma domestica Val) Sebagai Pencegah dan Pengobatan Penyakit Hati di Kelurahan Air Putih Kecamatan Tuah Madani Kota Pekanbaru - Al Fadhilah, Shafira; Wulan, Nimas; Zulfajri, Zulfajri; Fahriza, Mela; Marli, Nofrita; Nuraina, Nuraina; Syaputri, Rezy; Ramadhani, Ayu Indah; Sari, Seftika; Susanti, Emma; Octavia, Richa (Jurnal Mandala Pengabdian Masyarakat, 2024)
The liver is an organ that plays many roles in the body's metabolism. These include macronutrient metabolism, blood volume regulation, immune system support, lipid and cholesterol homeostasis, and breakdown of xenobiotic compounds, including various drugs. Hepatitis is one of the many diseases that is a major world health threat. One of the plants used to prevent and treat hepatitis is turmeric (Curcuma domestica Val) whose main content is curcumin. The Community Service Activities will be carried out on April 08 2023 at Air Putih Village, Tuah Madani District, Pekanbau City, Riau Province. The aim of this community service is to increase public understanding and awareness about the treatment and prevention of liver disease by using herbal plants and to see the level of public knowledge about diseases that attack the liver so it is hoped that this community service can improve the level of public health which will certainly help reduce the number of sufferers. liver disease. From the results of this service activity, it can be seen that the level of knowledge of each individual is different. The number of respondents obtained was 50 respondents, and the results showed that the majority had a good level of knowledge about liver disease after counseling and providing education with leaflets.